(untitled) (European Journal of Education and Psychology, 2011)
The purpose of the present study was to analyze the relationship between the whole family attitudes, values and interests toward sport and physical activity, and the ones of the children of the family (boys and girls). 355 adolescents age 12 to 22 from the Spanish regions of Basque Country and Cantabria took part in the study. There were administered the Family Sports Environment Questionnaire along with the Physical Self-Concept Questionnaire Scores derived from the questionnaires show a relationship between a good family sports environment and a higher physical self-concept and a more frequent practice of sports in adolescents. Differences on the family sports environment have been found depending on the gender of the studied adolescent. Girls perceived a worse family sports environment than boys. Also different perceptions were noticed depending on the gender of the other children of the family: the boys of families who only have sons perceived more positive environment than the boys of families with children of both genders. The worst perceptions were the ones of the girls who were the only child or who only had female siblings.